Osmotic Stress Modulates the Balance between Exocytosis and Clathrin-Mediated Endocytosis in Arabidopsis thaliana - Zwiewka, Marta; Nodzyński, Tomasz; Robert, Stéphanie; Vanneste, Steffen; Friml, Jiří (Molecular plant, 2015)
The sessile life style of plants creates the need to deal with an often adverse environment, in which water availability can change on a daily basis, challenging the cellular physiology and integrity. Changes in osmotic conditions disrupt the equilibrium of the plasma membrane: hypoosmotic conditions increase and hyperosmotic environment decrease the cell volume. Here, we show that short-term extracellular osmotic treatments are closely followed by a shift in the balance between endocytosis and exocytosis in root meristem cells. Acute hyperosmotic treatments (ionic and nonionic) enhance clathrin-mediated endocytosis simultaneously attenuating exocytosis, whereas hypoosmotic treatments have the opposite effects. In addition to clathrin recruitment to the plasma membrane, components of early endocytic trafficking are essential during hyperosmotic stress responses. Consequently, growth of seedlings defective in elements of clathrin or early endocytic machinery is more sensitive to hyperosmotic treatments. We also found that the endocytotic response to a change of osmotic status in the environment is dominant over the presumably evolutionary more recent regulatory effect of plant hormones, such as auxin. These results imply that osmotic perturbation influences the balance between endocytosis and exocytosis acting through clathrin-mediated endocytosis. We propose that tension on the plasma membrane determines the addition or removal of membranes at the cell surface, thus preserving cell integrity.
Keywords: Clathrin; Exocytosis; protein trafficking; clathrin-mediated endocytosis; Endocytosis; kyseliny indoloctové; fyziologická adaptace; Cell Membrane; Indoleacetic Acids; osmotický tlak; mutace; Arabidopsis Proteins; endocytóza; Gene Knockdown Techniques; proteiny huseníčku; auxin; osmotic stress; exocytóza; Mutation; Osmotic Pressure; genový knockdown; klathrin; buněčná membrána; Arabidopsis; Adaptation, Physiological